Risk Factors of Stunting in Infants Under Five Years - Asni Novita Harahap; Donal Nababan; Evawani Martalena Silitonga (TOUR HEALTH JOURNAL, 2022)
Purpose: Stunting is one of the problems that hinder human development globally. Stunting is a nutritional problem that must be considered for the sake of an advanced nation's generation. Adverse effects that can be caused by stunting are disruption of brain development, intelligence, impaired physical growth, and metabolic disorders in the body, decreased cognitive ability and learning achievement, decreased immunity so that you get sick easily, and a high risk of developing diabetes, obesity, heart disease and blood vessels, cancer, stroke and disability in old age. This will reduce the quality of Indonesia's human resources, productivity and competitiveness of the nation. The province of North Sumatra, the prevalence of stunting, is 30.11% and the district of Humbang Hasundutan, the prevalence of stunting under five is 41.3%. The purpose of this study is to find out what are the risk factors for stunting in toddlers in the working area of the Kampung Baru Health Center in Medan City in 2021. This research is an analytical research with a cross-sectional approach carried out in the working area of the Kampung Baru puskesmas, during January - December 2021. The population is mothers who have toddlers. Method: The sampling method was carried out by total sampling, namely the entire population was used as the research sample. The type of data is primary data through direct interviews guided by a questionnaire. Data analysis was carried out in stages including univariate, bivariate and multivariate analysis. Results: The results showed that there was a relationship between knowledge and stunting in toddlers (p value = 0.015). There is a relationship between parenting style and the incidence of stunting in toddlers (p value = 0.0347). There is no relationship between access to sanitation and the incidence of stunting in toddlers (p = 0.716). There is a relationship between socio-economic and Stunting Incidents in Toddlers (p value = 0.022). Disscusion and Conclusion: There is a relationship between socio-economic and the incidence of stunting in toddlers. The most dominant factor related to the incidence of stunting is knowledge.